The Role of the Karya Salemba Empat Scholarship Program in the Self and Social Development of Receiving Students (a Study at Riau University Campus) - Annisa Fitri; Bunari Bunari; Yuliantoro Yuliantoro (FKIP - Universitas Riau, 2026)
This study aims to analyse the role of the Karya Salemba Empat (KSE) Scholarship in developing the personal and social development of its recipients. Not only that, this scholarship also encourages students to play an active role in the campus environment and society. Data for this study was obtained through a descriptive qualitative approach with data collection methods including observation, interviews, and documentation. The results of the study indicate that the Karya Salemba Empat Scholarship plays an important role in providing financial assistance to students, thereby increasing their motivation and academic achievement during their studies. In addition, the implementation of this programme can increase the interest and talent, confidence, experience, time management, and optimistic drive for success of scholarship recipients, especially at the University of Riau. Furthermore, the Karya Salemba Empat Scholarship also aims to enable scholarship recipients to contribute to society through community development, which is in line with the third principle of the tri dharma of higher education, namely community service. Thus, the Karya Salemba Empat Scholarship not only provides economic assistance but also serves as an important facilitator in the process of student self-development and social development.